Liberdade de expressão e direito ao esquecimento: donflitos e intersecções entre direitos fundamentais - Almeida Filho, Sergio Baptista Pereira de (2024)
This dissertation examines the complex interaction between the fundamental rights of freedom of expression and the right to be forgotten. It analyzes the concept, foundations, and jurisprudential applications of these rights, focusing especially on current conflicts emerging from the digital era. Initially, the work explores the historical background and multiple theoretical facets of freedom of expression, a pillar of democratic societies. Subsequently, it discusses opposing views advocating limitations to this right, highlighting emblematic legal cases. The analysis then shifts to personality rights, studying their essence and legal protection mechanisms. Within this context, privacy rights and data protection are addressed, emphasizing the right to informational self-determination. Finally, the concept of the right to be forgotten is scrutinized theoretically and through comparative jurisprudence, balancing it with freedom of expression. Landmark legal cases in Brazil, the United States, the European Union, Germany and England are examined in-depth, revealing the complex equilibrium between remembering and forgetting in the digital age. Fundamentally, this dissertation argues for a conciliatory coexistence between freedom of expression and personality rights like privacy